The Effect of Trap Crop Kenikir Treatment on Soil Arthropod Population Dynamics in Chili Cultivation - Pratiwi, Vicha Rista; Aminatun, Tien (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2025)
This study aims to: (1) find out the soil arthropod family found in red chili (Capsicum annum L.) cultivation with trap crop treatment of walnut plants (Tagetes erecta L.). (2) to determine the effect of trap crop treatment of walnut plants (Tagetes erecta L.) on red chili (Capsicum annum L.) cultivation on soil arthropod population dynamics. Data collection was carried out using the pitfall trap method. The population in this study is all soil arthropods found in red chili plantation areas, then the sample from this study is soil arthropods that are trapped in the pitfall trap. This research took place during August 2021-December 2021 with 5 data collections. The data taken included climatic and edapic data on each observation as well as all types of soil arthropods on red chili plantations. The data obtained were analyzed using descriptive analysis which included the diversity index, equality index, and dominance index. The results of the study showed that 17 families of soil arthropods were obtained. The population dynamics of soil arthropods in red chili cultivation have changed over time by showing ups and downs in yields. Habitat modification with trap crop of kenikir plants as a treatment did not have a significant effect on the population dynamics of soil arthropods in chili cultivation